Perkembangan Anak Usia Remaja dalam Aspek Perilaku dan Emosional - Mahardika, I Ketut; Alega, Sestritama; Vira, Afiva Aisha; Hilmi, Nurmala Chamelia (Peneliti.net, 2024)
Development, namely growth or evolution and decline or involution, occurs simultaneously in human life. However, these two processes never stop throughout human life. During adolescence, physical growth becomes the prima donna of growth compared to other parts, but in old age, physical decline and changes in the mind change more than others. Adolescence is an important period in the life span, a transitional period, a period of change, a problematic age, a period where individuals search for self-identity, a scary age (dreaded), a period of unrealism, and the threshold towards maturity. During adolescence, cognitive development has reached the peak stage, namely the formal operations stage (11 years - adulthood) (Gunarsa, 1982); a capacity for abstract thinking, where adolescent reasoning is more similar to the way scientists seek solutions to problems in the laboratory.